Książka jako „złoty standard” w naukach humanistycznych i społecznych - Melosik, Zbyszko (Studia Edukacyjne, 2019)
The article is devoted to the role of monographs in university humanisties and social sciences. The various contexts of the main problem are analysed with the special attention to the academic promotion and the „writing as a thinking” thesis. At the end the pedagogical role of the bookas a source of linea thinking is considered.against the backgroung of the growing dominance of virtual culture.